2009
DOI: 10.1007/s00296-009-1003-7
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse proliferative glomerulonephritis associated with dermatomyositis with nephrotic syndrome

Abstract: We described a 44-year-old man developing dermatomyositis (DM) and nephrotic syndrome (NS). Renal biopsy revealed diffuse proliferative glomerulonephritis (DPGN) with depositions of immunoglobulin and complements. A combination therapy of steroid and cyclophosphamide (CTX) was found very effective for the patient. Chronic glomerulonephritis is rare in DM. In our review of related literature, membranous glomerulonephritis (MN) is the main type of glomerular lesion, another type is mesangial proliferative glomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…It has been suggested that there are 2 possible mechanisms for renal damage in these patients: tubular disorder related to myoglobulinemia and myoglobinuria and, less frequently, chronic glomerulonephritis. There are also cases reported with membranous and mesangial proliferative glomerulonephritis [11]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that there are 2 possible mechanisms for renal damage in these patients: tubular disorder related to myoglobulinemia and myoglobinuria and, less frequently, chronic glomerulonephritis. There are also cases reported with membranous and mesangial proliferative glomerulonephritis [11]. …”
Section: Discussionmentioning
confidence: 99%
“…First, rhabdomyolysis with release of myoglobin can lead to acute tubular necrosis with deterioration of renal function [14,15]. Second, several reports revealed the occurrence of chronic glomerulonephritis in patients with PM/DM [14,46-49]. In PM, mesangial proliferative glomerulonephritis represents the leading glomerular lesion [46,50,51].…”
Section: Reviewmentioning
confidence: 99%
“…In contrast, the predominant finding in DM with renal involvement is membranous nephropathy [55-57]. Nevertheless, both mesangial proliferative glomerulonephritis [58] and diffuse proliferative glomerulonephritis [49] have been reported in single case reports.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic glomerulonephritis is quite rare in dermatomyositis. To date, based on our search, only 8 cases of documented glomerulonephritis have been reported [3–10]. In four cases dermatomyositis and glomerulonephritis developed concurrently and in the rest of cases glomerulonephritis presented 1.5–9 years after the diagnosis of dermatomyositis.…”
Section: Discussionmentioning
confidence: 99%